2016
DOI: 10.1111/all.12907
|View full text |Cite
|
Sign up to set email alerts
|

Increased microRNA-323-3p in IL-22/IL-17-producing T cells and asthma: a role in the regulation of the TGF-β pathway and IL-22 production

Abstract: Our data suggest that miR-323-3p acts in a negative feedback loop to control the production of IL-22 in IL-22/IL-17-producing T cells and might thus impact the T-cell responses in asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 51 publications
4
34
0
Order By: Relevance
“…Decreased expression of miR-26a was previously detected in IL-22-producing T cells, which play an important role in allergic diseases. 25 Variations of miR-26a and its targeted gene HAS3 might play a significant role in the abnormality of the skin barrier in patients with AD.…”
Section: Discussionmentioning
confidence: 99%
“…Decreased expression of miR-26a was previously detected in IL-22-producing T cells, which play an important role in allergic diseases. 25 Variations of miR-26a and its targeted gene HAS3 might play a significant role in the abnormality of the skin barrier in patients with AD.…”
Section: Discussionmentioning
confidence: 99%
“…Some miRNAs have been recognized as important regulators of allergic inflammation . MiR‐323‐3p can control the production of IL‐22 in IL‐22/IL‐17‐producing T cells via a negative feedback loop and impact the T‐cell responses in asthma . In addition, miRNA‐155 is essential to dendritic cells for the initiation and maintenance of allergic airway inflammation.…”
Section: Risk Factorsmentioning
confidence: 99%
“…26 MiR-323-3p can control the production of IL-22 in IL-22/IL-17-producing T cells via a negative feedback loop and impact the T-cell responses in asthma. 27 In addition, miRNA-155 is essential to dendritic cells for the initiation and maintenance of allergic airway inflammation. The deficiency of miRNA-155 can alleviate allergic airway inflammation by reducing Th2 immune reaction and ATP-/P2R-induced activation of dendritic cells in mice, which suggests that miRNA-155 is a potential therapeutic target for allergic airway disease.…”
mentioning
confidence: 99%
“…For example, the expression of miR-323-3p in IL-22/IL-17-producing T cells increased in patients with asthma and atopic dermatitis. Study has demonstrated that miR-323-3p may suppress STAT3 mRNA, whereas TGF-β may promote Th22 cells (Kärner et al, 2016). Upon accumulation of IL-22 and IL-17, miR-323-3p produced by T cells inhibits the expression of SMAD2, SMAD3, and STAT3, resulting in diminished production of IL-22.…”
Section: Roles Of Mirnas In Tgf-β-dependent T Cells' Differentiation mentioning
confidence: 99%